Community care of the physically disabled due to leprosy - R Ganapati (Wolters Kluwer Medknow Publications, 2011)
This preliminary presentation based on extensive field studies carried out by Bombay Leprosy Project, a research-oriented NGO, portrays the alarming dimensions of the disease burden felt by rural communities and recommends a cost effective field model. This study in an adopted rural population in Shahapur "taluka" of Thane District assumes tremendous significance and is worthy of replication in comparable situations. This is particularly so in the background of the absence in the literature of any similar field studies based entirely on community care of the physically disabled due to leprosy. The magnitude of the problem posed by leprosy patients with disabilities and their rehabilitation is highly challenging and is expected to pose a heavy burden on the community as well as unprecedented strain on the PHCs managed by the government. The health planners should rethink on future strategies in such a manner that human rights of the downtrodden patients suffering from the "neglected disease" of leprosy are not sidelined